2013
DOI: 10.1002/ca.22303
|View full text |Cite
|
Sign up to set email alerts
|

Bony landmarks of the medial orbital wall: An anatomical study of ethmoidal foramina

Abstract: The study determines the distribution patterns of ethmoidal foramina (EF) evaluate how they are affected by gender or bilateral asymmetry, and highlights the surgical implications on the anatomical landmarks of the orbit. Two hundred and forty-nine dry orbits were assessed. The number and pattern of EF were determined and distances between the anterior lacrimal crest (ALC), anterior (AEF) middle (MEF), posterior (PEF) ethmoidal foramina and between PEF and the optic canal (OC) were measured. The patterns of EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
2
21
2
Order By: Relevance
“…The AEF and PEF are usually located on the FES (Kirchner et al, ; Standring, ; Piagkou et al, ), but can also be located superiorly (on the frontal bone) or inferiorly (on the ethmoid bone) to the FES. Depending on their location on the ethmoid bone or frontal bone, this may increase the risk of injury to underlying structures such as the ethmoidal cells (Kazak et al, ) or CSF leakage (Takahashi et al, ; Takahashi et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The AEF and PEF are usually located on the FES (Kirchner et al, ; Standring, ; Piagkou et al, ), but can also be located superiorly (on the frontal bone) or inferiorly (on the ethmoid bone) to the FES. Depending on their location on the ethmoid bone or frontal bone, this may increase the risk of injury to underlying structures such as the ethmoidal cells (Kazak et al, ) or CSF leakage (Takahashi et al, ; Takahashi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In trauma for example, the incidence of isolated medial orbital wall fractures occur as frequently as 55% (Choi and Flores, ), and zygomaticomaxillary complex fractures of the lateral orbital wall occur in 10% of the human population (Lee et al, ). Depending on the type of injury, reconstructive surgeries of the orbit may include optic nerve (ON) decompression, reconstruction of the skull base, fracture repair, tumor resection and endoscopic sinus surgeries (Han et al, ; Mutalik et al, ; Piagkou et al, ). To avoid complications and damage, it is essential for surgeons to have an adequate and precise knowledge of the orbital foramina and their important neurovascular structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1.3 ) [ 19 ]. Piagkou et al found high anatomic variation, however, with anywhere from 1 to 6 ethmoidal foramina present in 249 human orbit specimens, with 61 % having 2 foramina [ 20 ].…”
Section: Osteologymentioning
confidence: 94%